Spatial soil loss risk and reservoir siltation in semi-arid Tunisia - Jebari, S.; Berndtsson, R.; Bahri, Akissa; Boufaroua, M. (Informa UK Limited, 2010)
Soil erosion vulnerability and extreme rainfall characteristics over the Mediterranean semi-arid region of Tunisia are crucial input for estimation of siltation rate in artificial reservoirs. A comprehensive high resolution database on erosive rainfall, together with siltation records for 28 small reservoirs, were analysed for this region, the Tunisian Dorsal (the easternmost part of the Atlas Mountains). The general life-span of these reservoirs is only about 14 years. Depending on the soil degradation in the different catchments, the corresponding reservoirs display a wide range of soil erosion rates. The average soil loss was 14.5 t ha-1 year-1but some catchments display values of up to 36.4 t ha-1 year-1. The maximum 15-min duration rainfall intensity was used to determine the spatial distribution of rainfall erosivity. The northwestern parts of the Tunisian Dorsal display the most extreme rainfall erosivity. Spatial erosion patterns are to some extent similar; however, they vary greatly according to their location in the "soil degradation cycle?. This cycle determines the soil particle delivery potential of the catchment. In general, the northwestern parts of the Dorsal display modest soil erosion patterns due to the already severely degraded soil structure. Here, the soil surface is often the original bedrock. However, the greatest soil erosion occurs in the mid-eastern parts of the Dorsal, which represents the "degradation front?. The latter corresponds to the area with highest erosion, which is continuously progressing westward in the Dorsal. The large variation between the erosive rainfall events and the annual soil loss rates was explained by two important factors. The first relates to the soil degradation cycle. The second factor corresponds to the degradation front with the highest soil loss rates. At present this front is located at 300 m altitude and appears to be moving along an 80-km westward path starting from the east coast. A better understanding of the above can be used to better manage soils and soil covers in the Tunisian Dorsal area and, eventually, to decrease the soil erosion and reservoir siltation risk.